Integrated Analysis of Metabolome and Transcriptome Reveals Insights for Cold Tolerance in Rapeseed (Brassica napus L.) - Raza, Ali; Su, Wei; Hussain, Muhammad Azhar; Mehmood, Sundas Saher; Zhang, Xuekun; Cheng, Yong; Zou, Xiling; Lv, Yan (Frontiers in Plant Science, 2021)
Rapeseed (Brassica napus L.) is an important oilseed crop in the world. Nevertheless, its productivity is significantly influenced by numerous abiotic stresses, including cold stress (CS). Consequently, enhancement in CS tolerance is becoming an important area for agricultural investigations and crop improvement. Therefore, the current study aimed to identify the stress-responsive genes, metabolites, and metabolic pathways based on the combined transcriptome and metabolome analysis to understand the CS responses and tolerance mechanisms in the cold-tolerant (C18) and cold-sensitive (C6) rapeseed varieties. Based on metabolome analysis, 31 differentially accumulated metabolites (DAMs) were identified between different comparisons of both varieties at the same time points. From the transcriptome analysis, we detected 2845, 3358, and 2819 differentially expressed genes (DEGs) from the comparison of C6-0_vs_C18-0, C6-1_vs_C18-1, and C6-7_vs_C18-7. By combining the transcriptome and metabolome data sets, we found that numerous DAMs were strongly correlated with several genes (DEGs). Functional enrichment analysis of the DAMs and the correlated DEGs specified that most DEGs and DAMs were mainly enriched in diverse carbohydrates, amino acids metabolisms. Among them, starch and sucrose metabolism and phenylalanine metabolism were significantly enriched and played a vital role in CS adaption of rapeseed. Six candidate genes were selected from the two pathways for controlling the adaption to low temperature. In further validation, the T-DNA insertion mutants of their Arabidopsis homologous, including 4cl3, cel5, fruct4, ugp1, axs1, and bam2/9 were characterized, and six lines differed significantly in levels of the freezing tolerance. The current study's outcome provided new prospects to understand the molecular basis of CS responses and tolerance mechanisms in rapeseed and present a set of candidate genes for use in improving CS adaptability in rapeseed.